Photophysics of GFP-related chromophores imposed by a scaffold design. Issue 24 (1st March 2016) - Dolgopolova, E. A.; Moore, T. M.; Fellows, W. B.; Smith, M. D.; Shustova, N. B.
Abstract : In this paper, a rigid scaffold imposes the photophysics of chromophores with a benzylidene imidazolidinone core by mimicking the β-barrel structure of the green fluorescent protein (GFP) and its analogs. Abstract : In this paper, a rigid scaffold imposes the photophysics of chromophores with a benzylidene imidazolidinone core by mimicking the β-barrel structure of the green fluorescent protein (GFP) and its analogs. The designed artificial frameworks maintain fluorescence responses and, therefore, conformational rigidity of typically non-emissive GFP-related chromophores. To replicate a small weight percent of the chromophore inside the natural GFP, two synthetic approaches were utilized: coordinative immobilization and non-coordinative inclusion. Despite low chromophore loading in the rigid matrix, both approaches resulted in formation of photoluminescent hybrid materials. Furthermore, the rigid scaffold dictates chromophore fluorescence by replicating its behavior in solution or the solid state. The presented results open an avenue for utilization of rigid scaffolds in the engineering of materials with tunable photoluminescence profiles for a variety of practical applications.